Pelatihan Penggunaan Mendeley dalam Meningkatkan Keterampilan Menulis Karya ilmiah Mahasiswa Prodi Pendidikan Sejarah Universitas Jambi - Yosephine Sinurat, Junita; Yaldi, Destri; Mustofa Meihan, Andre; Mareta, Yoan; Rukmana, Lisa (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
This service activity aims to provide training in the use of Mendeley to Jambi University History Education students to overcome various problems faced by students in writing scientific papers. Students often encounter problems or problems in writing, for example: 1) lack of consistency in the theme/title with the content of the writing, 2) unfocused problem formulation, 3) sub-chapters are less detailed, 4) quotations in the literature review are not relevant to the bibliography, 5) Conclusion does not describe the content of the writing, 6) EYD is not correct, and 7) writing system is not guided by applicable writing standards. Mendeley is an application that can be used to make it easier for students to cite and compile bibliography in writing scientific papers in a more efficient way. This training activity was carried out in three stages, namely preparation, training implementation and evaluation. It is hoped that this training can be a positive motivation for students and be able to improve their skills in writing scientific papers which will also have an impact on improving the quality of students' scientific work within Jambi University.